The Battle of Stalingrad and the Second Front Problem - V. O. Pechatnov (Vestnik MGIMO-Universiteta)
Using less-known documents from American and British archives the article examines the impact of developments on Soviet-German front in late 1942 on military-political planning in U.S. and U.K. with a special emphasis on the second front problem. It is demonstrated how deeply the German defeat at Stalingrad affected Anglo-American military and intelligence estimates of situation at Soviet- German front and prospects of the war in general.